Fiber reinforced plastic overlay retrofit of hollow clay tile masonry infilled reinforced concrete frames - Hanoğlu, Kemal Burak. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering , 2002., 2002)
Stiffness and strength contribution of hollow clay tile infills to ductile and non-ductile reinforced concrete frames were evaluated using 1:3 scale specimens tested under quasi-static reversed cyclic seismic loads. Four ductile and four non-ductile framed single-bay-single-story specimens with and without infill panels were tested in tandem specimen configuration simulating the seismic actions on lowest interior spans of typical of low-rise infilled frame structures. During the tests on masonry infill material, the testing procedures originally developed for solid brick masonry were shown unsuitable for the hollow clay tile masonry testing. A new method for tensile strength testing of the hollow clay tile units was proposed and used coupling with finite element models to establish a tile tensile strength estimate. Infilled frames with plain hollow clay tile infill were shown to have failure loads well in excess of the bare frames. Glass fiber woven sheet and carbon fiber reinforced plastic laminates were used to confine and brace the hollow clay tile infill. Addition of glass-fiber overlays and carbon fiber laminates increased the strength of the infilled frames above the conventionally infilled frames. However, the maximum displacement capacity of the new system reduced due to low compressive strength of the tile infill, which confined the failures and deformations to infill corners and column mid-height. A new finite element modeling approach was developed based on the use of plane-framework analysis methods for plane stress analysis. Two different model scales were considered to show the capabilities of the proposed approach and the possibilities of simplification for engineering office use. A standard finite element analysis package with point-wise nonlinear element capability was used to calculate the pushover curve of the tested specimens. The results showed a good agreement with the test results for the detailed model, and the engineering model was regarded amenable for further calibration.
Keywords: Reinforced concrete.; Concrete construction.; Reinforced concrete construction.; Reinforced plastics.